Computer Algorithm for Counting and Measuring Alpha Particles Track Diameters in CR-39 Detectors - Mushtaq Al-Jubbori; Salah Al-Shumaisy (Jordan Journal of Physics, 2025)
This work is concerned with the design and test of a Matlab-2012 computer algorithm capable of performing image processing operations on digital images of alpha particles tracks onCR-39 detectors. The software measures the diameters of individual tracks separately and registers the measured value of each diameter on the digital picture. It also calculates the mean and standard deviation for all tracks within any particular view. In addition to the enhanced measurement accuracy resulting from the elimination of sources of human errors associated with microscope measurements, the software saves a great deal of manual effort compared with the method currently being used for the study of nuclear tracks. The use of the software in the analysis of 2, 2.5, 3.1 MeV alpha particles tracks on CR-39 detector etched with 6.25 N NaOH solution at (70±1)oC resulted in the ability to reach some empirical relations describing the tracks diameters as functions of alpha particles energy and etching solution temperature. Keywords: CR-39 detectors; Alpha diameters modeling; Empirical relations; Matlab.